Cross-Configured Wideband Multiple-Input Multiple-Output Antenna with Defected Ground Structure and Parasitic Directors for 2.7–12 GHz Ultra-Wideband and Sub-6 GHz Wireless Applications - Rami Abduimawjood Mohammed; Uttam Laxman Bombale (Universitas Ahmad Dahlan, 2026)
Modern Ultra-Wideband (UWB) and sub-6 GHz systems require compact antennas with wide bandwidth, enhanced gain, low coupling, and reliable diversity. This study develops a simulation-based wideband MIMO antenna that addresses the bandwidth and isolation limitations of conventional planar microstrip antennas. The research contribution is a progressive antenna family based on a microstrip-fed planar slot radiator using a partial defected ground structure, parasitic directors, and a lens-shaped substrate. The design is modeled in Ansys HFSS through four stages: an optimized single element, a 1×2 MIMO antenna, a cross-configured 4-port MIMO antenna, and a 1×4 MIMO antenna. The defected ground structure improves impedance matching, whereas the directors and lens-shaped substrate enhance forward radiation. The optimized single antenna achieves a simulated -10 dB impedance bandwidth of 2.72–12.0 GHz and peak gains of 5.54, 6.79, and 6.21 dB at 6.7, 8.7, and 10.7 GHz, respectively. The 1×2 MIMO antenna preserves a 2.7–11.8 GHz bandwidth and achieves gains of 9.25, 9.94, and 8.88 dB, with a worst-case ECC of 0.0038 and a minimum diversity gain of 9.9999 dB. The cross-configured 4-port MIMO antenna provides the highest gains of 9.31, 9.99, and 9.89 dB, confirming the benefit of the orthogonal arrangement. The 1×4 MIMO antenna shows lower gains of 1.253, 1.254, and 1.261 dB, but provides strong diversity, with adjacent- and non-adjacent-port ECC values below 0.0021 and 0.0010, respectively. The results confirm that the proposed antenna family provides a practical trade-off between bandwidth, gain, isolation, and diversity for ultra-wideband, sub-6 GHz, IoT, sensing, and high-data-rate wireless applications.